Mobility Matters: the ERASMUS Impact Study - Brandenburg, Uwe; Taboadela, Obdulia; Vancea, Mihaela (International Higher Education, 2015)
Mobility has impact on the career and the personal. Most importantly, personality traits such as confidence or tolerance are not only predictors for studying abroad but also relevant for employability. These are some results of one of the largest studies ever conducted on Erasmus: the Erasmus Impact study (EIS).